Perlindungan Hukum Terhadap Usaha Mikro, Kecil, Dan Menengah Dalam Upaya Penguatan Ekonomi Masyarakat Di Kecamatan Kampar - Dasrol, Dasrol; Lestari , Rika; Darnia, Meriza Elpha (Universitas Medan Area, 2024)
The research aims to determine the legal protection of UMKM in an effort to strengthen the community's economy in the Kampar sub-district. This research uses the Sociological method. In order to find out how the implementation of existing regulations related to legal protection for UMKM and the extent of their effectiveness in supporting the economic growth of UMKM in Kampar District and the main challenges faced by UMKM in Kampar District in obtaining legal protection in running their businesses. Micro, small and medium enterprises (UMKM) in Indonesia are one of the sectors that make a large and significant contribution to national economic development. This is because the existence of UMKM has proven to be able to drive the economy and reduce the number of unemployed people. UMKM are regulated in Law of the Republic of Indonesia Number 20 of 2008 concerning UMKM. The government has actually provided protection for UMKM as formulated in Article 35 Paragraph (1) of Law No. 20 of 2008 concerning Micro, Small and Medium Enterprises, that “Large enterprises are prohibited from owning or controlling micro, small and medium enterprises as their business partners in the implementation of partnership relationships.” However, in practice this has not been effective given the absence of a supervisory mechanism from the government. On the other hand, this provision is considered only a formality, so that the goal of empowering national entrepreneurs or UMKM is not achieved.